Synthesis and X-ray single crystal study of 5-(4,4,5,5 – tetramethyl – 1,3,2 –dioxoborolane) – 10,20 – diphenylporphyrin - Nuur Haziqah Mohd Radzuan; Nawwar Hanun Abdul Malek; Mohammad Fadzley Ngatiman; Tan Ke Xin; Mohd Bakri Bakar; Nurul Izzaty Hassan; Muntaz Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Borylated porphyrin is one of building blocks in coupling reactions to obtain the multiporphyrin containing two, three or more subunits of porphyrins. In this study, one of borylated porphyrin derivatives, 5-(4,4,5,5 – tetramethyl – 1,3,2 – dioxoborolane) -10,20 – diphenylporphyrin (B-DPP) was synthesized through four steps of reactions. The building block of porphyrin, dipyrromethane was synthesized through a condensation reaction in the presence of trifluoroacetic acid as catalyst. Subsequently, A2B2 type of porphyrin was obtained by Lindsey condensation reaction followed by bromination reaction to produce porphyrin halide. Suzuki cross coupling reaction between porphyrin halide and pinacolborane with Pd (II) catalyst afforded 40% of borylayed porphyrin. The product was successfully characterized by using nuclear magnetic resonance spectroscopy (NMR) and UV-Visible spectroscopy (UV-Vis). This compound crystallized from a mixture of dichloromethane/methanol to give violet needle-like crystal. Crystallographic studies showed this compound crystallized in monoclinic system with space group of P21/c.